2012
DOI: 10.1186/1756-9966-31-95
|View full text |Cite
|
Sign up to set email alerts
|

Pro-death and pro-survival properties of ouabain in U937 lymphoma derived cells

Abstract: BackgroundEpidemiological studies revealed significantly lower mortality rates in cancer patients receiving cardiac glycosides, which turned on interest in the anticancer properties of these drugs. However, cardiac glycosides have also been shown to stimulate cell growth in several cell types. In the present investigation we analyzed the pro-death and pro-survival properties of ouabain in the human lymphoma derived cell line U937.MethodsROS, intracellular Ca++, cell cycle were evaluated by loading the cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Several work reported that bufalin or ouabain could cause ROS generation in human colon or lymphoma cancer cells . We here provide further evidence showing the production of ROS in human NSCLC cells upon the CGs treatment.…”
Section: Discussionsupporting
confidence: 73%
“…Several work reported that bufalin or ouabain could cause ROS generation in human colon or lymphoma cancer cells . We here provide further evidence showing the production of ROS in human NSCLC cells upon the CGs treatment.…”
Section: Discussionsupporting
confidence: 73%
“…Intracellular ROS plays an important role in inducing apoptosis in cancer cells. Previous study showed that Ouabain elevated the cytosolic ROS level in U937 cells [23] and neuroblastoma cell line SH-SY5Y cells [24]. In order to investigate if Peruvoside also induced ROS production in KG1a and K562 leading to apoptosis, we assessed the ROS level in these cells by flow cytometry 24 h after Peruvoside treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 8−10 discrete foci in each section were examined at 400× to generate an average staining intensity and percentage of stained cells. The final H-score was calculated using the formula: [(1×percentage of weakly stained tumor cells)+(2×percentage of moderately stained tumor cells)+(3×percentage of intensely positive tumor cells)] 34…”
Section: Methodsmentioning
confidence: 99%